When is a "free" registrar in clinic not free?. (20th December 2011) - Lota, Amrit S; Manisty, Charlotte H; Sutton, Richard; Francis, Darrel P
Abstract : Objective To investigate whether using registrars (doctors undergoing higher specialist training, whose salary is reimbursed) rather than consultants in outpatient clinics saves money Design Development of a formula calculating the economic breakeven point and application to retrospective audit data from 273 outpatient consultations. Setting General cardiology outpatient clinic in a secondary and tertiary referral NHS hospital. Outcomes Difference in probability of a registrar and a consultant making a diagnostic decision that completes a clinical episode. Use of UK costings for consultant salaries and outpatient attendances to determine the economic breakeven point. Results The formula showed that if a registrar's episode completing probability is 12 percentage points lower than that of a consultant, then using a registrar costs the hospital more. Real life data showed that episode completion probabilities are 43 percentage points lower for registrars than for consultants (26% versus 69%, 95% CI 32% to 54%, P<0.0001). Conclusion It is wrong to assume that external reimbursement of registrar salaries makes them a money saving option for staffing clinics. The apparent service role of a registrar can be a disservice.